Practical long‐term storage of strawberries in refrigerated containers at ice temperature. Issue 9 (5th August 2020) - Ikegaya, Atsushi; Ohba, Seiji; Nakajima, Teruko; Toyoizumi, Tomoyasu; Ito, Seiko; Arai, Eiko
Abstract: This study investigated the effect of storage temperature in the presence or absence of film packaging on the Benihoppe and Kirapika varieties of Japanese strawberries stored for 28 days at 0°C and 3°C. The study was conducted in a 20‐foot reefer container for practicality. Storage at 0°C suppressed decay and reduction in sugars and organic acids more efficiently than that at 3°C. Softening of fruit hardness was also suppressed depending on the variety. The reduction in sugars and organic acids did not affect strawberry palatability. Along with low temperature, long‐term storage of strawberries also requires the use of film packaging, which prevents drying. Without film packaging, storage at both 0°C and 3°C decreased fresh weight significantly, resulting in loss of commercial value. In contrast, storage in film packaging decreased weight reduction to <5%, even after 28 days cold storage. Abstract : Storage at 0°C suppressed decay, and reduction of sugars and organic acids more efficiently than that at 3°C. Along with low temperature, long‐term storage of strawberries also requires the use of film packaging, which prevents drying. Without film packaging, storage at both 0°C and 3°C decreased fresh weight significantly, resulting in loss of commercial value. The proposed method can enhance the storage period of strawberries to 28 days or more.